2023
DOI: 10.3389/fpsyg.2022.1066146
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact in multiple adolescents’ contexts: The Intergroup Contact Interactions Scale (ICIS)

Abstract: In the present contribution, we aimed to test the psychometric properties of the Intergroup Contact Interactions Scale (ICIS). The ICIS is a tool that can easily be administered to assess ethnic minority and majority adolescents’ positive and negative intergroup contact in both school and out-of-school contexts. Study I included 169 adolescents in Italy (40.2% ethnic minority adolescents; 51.5% female; Mage = 14.41) and provided initial support for the two-factor structure (i.e., positive and negative contact)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Intergroup Contact Interactions Scale (Karataş et al, 2022 ; see also Table S2 for the standardized factor loadings and fit indices at T 1) was employed to assess adolescents' positive and negative contact in schools. Initially, participants were asked to think about their own interactions with outgroup members in school during the last 6 months by providing the following prompt: “The following questions are about interactions you may have had in school with people of foreign origin [Italian people].…”
Section: Methodsmentioning
confidence: 99%
“…Intergroup Contact Interactions Scale (Karataş et al, 2022 ; see also Table S2 for the standardized factor loadings and fit indices at T 1) was employed to assess adolescents' positive and negative contact in schools. Initially, participants were asked to think about their own interactions with outgroup members in school during the last 6 months by providing the following prompt: “The following questions are about interactions you may have had in school with people of foreign origin [Italian people].…”
Section: Methodsmentioning
confidence: 99%
“…In the validation study (Karataş, Rubini, et al, 2023), the ICIS was found to show an excellent two‐factor structure (i.e., positive and negative contact) in both school and out‐of‐school contexts, and measurement invariance across ethnic minority and majority adolescents was also established. In order to further support the distinction between valence and contexts, a confirmatory factor analysis (CFA) with four latent factors (i.e., positive contact in school, negative contact in school, positive contact in out‐of‐school context, and negative contact in out‐of‐school contexts) and 20 observed indicators (five per latent factor) was conducted in the present study.…”
Section: Methodsmentioning
confidence: 95%
“…Adolescents' positive and negative contact in school and out‐of‐school contexts were assessed with the Intergroup Contact Interactions Scale (ICIS; Karataş, Rubini, et al, 2023). Initially, participants were asked to think about their own interactions with outgroup members in the school context [out‐of‐school contexts such as public places, sports groups] during the last 6 months by providing the following explanation: “The following questions are about interactions you may have had in school [out‐of‐school] with people of foreign origin [Italian people].…”
Section: Methodsmentioning
confidence: 99%